Magnetic resonance diffusion‐weighted imaging: reproducibility of regional apparent diffusion coefficients for the normal fetal brain. (3rd January 2013) - Boyer, A. C.; GonÇalves, L. F.; Lee, W.; Shetty, A.; Holman, A.; Yeo, L.; Romero, R.
ABSTRACT Objective To evaluate the reproducibility of regional apparent diffusion coefficient (ADC) measurements of the normal fetal brain in the second and third trimesters of pregnancy. Methods Fifty normal singleton fetuses from healthy pregnant women between 19 and 37 weeks' gestation were studied without sedation. Single‐shot diffusion‐weighted images of the fetal brain were obtained using a 1.5‐Tesla magnetic resonance scanner and a six‐channel body array coil. ADC maps were created using 0 and 1000 b‐values along three orthogonal directions. Two examiners independently measured ADC values in the cerebellar hemispheres (CH), pons, thalamus, basal ganglia (BG), centrum semiovale (CSO), and frontal (FWM), parietal (PWM), temporal (TWM) and occipital (OWM) white matter. Correlation between ADC values and menstrual age was assessed by linear regression analysis. The bias and agreement of ADC measurements were determined using Bland–Altman plots. Results ADC values either remained constant (BG, FWM, PWM, TWM, OWM, CSO) or decreased (CH, pons, thalamus) with advancing menstrual age. Mean intraobserver bias for ADC measurements was not significantly different from zero. Small interobserver differences in mean ADC measurements (i.e. a small mean bias) were detected for CH (1.26 ± 0.20 vs 1.20 ± 0.18 μm2/ms, P = 0.006), PWM (1.37 ± 0.29 vs 1.33 ± 0.26 μm2/ms, P = 0.02) and CSO (1.36 ± 0.29 vs 1.33 ± 0.28 μm2/ms, P < 0.0001). Measurement agreement was acceptable. Conclusions ADC measurements in normal unsedated fetuses in the second and third trimesters are reproducible except for small differences for PWM, CH and CSO between examiners.